ECOCULTURAL CITY – HOW ACTUAL IS THIS CONCEPT IN THE ERA OF DISRUPTION OF PANDEMIC COVID 19? - Winny Astuti; Rufia Andisetyana Putri; Hakimatul Mukaromah; Murtanti Jani Rahayu; Paramita Rahayu; Erma Fitria Rini; Isti Andini (Journal of Architecture&ENVIRONMENT, 2021)
This research explored the implementation of concept of Surakarta ecocultural city platform in the era of Pandemic Covid-19 in 2 case study areas of Balekambang Park as the Natural and Heritage Park and Jayengan Jewelry Kampung (JKP) as Heritage Creative Industry-based Kampung Tourism. Eco city is basically the concept to create new urban development to be more ecologically, liveable and Sustainable, while the cultural city refers to the city, which focusing on cultural and performance for branding the city.  Ecocultural city is mainly related to connectivity among people, place and culture and this concept is mostly applicated in the tourism world, where to maintain this sustainably, this has to address people, place and its cultural relationship with biophysical aspects. Therefore, in the era of disruption of COVID-19, the ecocultural based of tourist destination areas are highly affected due to the loss of tourists visiting the areas. The research found that the model of People, place, technology and government proposes for increasing adaptability of people to the disruption condition, initiating resilient, creative, healthy and smart places, exhalating technology for added value of tourism product and improving resilience  government to adapt, absorb the change, collaborating multi stakeholder partnerships